Optimising sampling methods for small mammal communities in Neotropical rainforests - Bovendorp, Ricardo S. [UNESP]; McCleery, Robert A.; Galetti, Mauro [UNESP] (Wiley, 2017)
Quantifying mammalian biodiversity is a critical yet daunting challenge, particularly in species-rich ecosystems. Non-volant small mammals account for >60% of the mammalian diversity and often require several survey methods to estimate their species richness and abundance, because of differences in their size and behaviour. Using 117 studies at 278 sites in a species-rich biome, the Brazilian Atlantic Forest, we determined the influence of trap configuration, trap type, and sampling effort on measures of species richness and abundance. We used generalised linear mixed-effects models to determine which methodological approaches influenced estimates of species richness and abundance at the sampling sites. We used estimates of beta (β) to determine which methods improved species richness and abundance estimates, and generated predicted values for the overall species richness as a function of trap configuration (line transect, grid, or both), trap type (pitfall traps, live-traps or both), and sampling effort (number of trap-nights). Our results indicated that sites in which pitfall traps alone were used generated higher estimates of the overall small mammal species richness and abundance, and rodent abundance, than sites in which only live-traps were used. Sites in which pitfall traps alone were used also produced higher estimates of species richness and abundance, and rodent species richness and abundance, than sites in which both trap types were used. Increased sampling effort led to increased estimates of species richness, but sites in which pitfall traps were used alone or together with live-traps had higher estimates of species richness with less sampling effort than sites in which live-traps only were used. Using pitfall traps greatly reduced the number of trap-nights necessary to obtain a good estimate of small mammal species richness in a community. We found no influence of trap configuration (line transects or grids) on estimates of species richness, but the abundance of rodents was estimated to be higher in sites where both line transects and grids were used, than in sites where only one trap configuration was used. Our review shows the importance of using pitfall traps in research, monitoring, and environmental impact studies on species-rich small mammal communities.
Keywords: biodiversity hotspots; communities; Cricetidae; Didelphimorphia; sampling methods